Obesity is associated with poorer range of motion and Tegner scores following hamstring autograft anterior cruciate ligament reconstruction in Asians - Abd Razak, Hamid Rahmatullah Bin; Chong, Hwei-Chi; Tan, Hwee-Chye Andrew (Annals of Translational Medicine; Vol 5, No 15 (August 06, 2017): Annals of Translational Medicine (Focus on “Myokines, Exercise and Cardiovascular Disease”), 2017)
Background: Current literature reporting on the impact of BMI on outcomes of orthopaedic surgical procedures is varied and inconsistent. The purpose of our study was to evaluate if body mass index (BMI) affects outcomes of primary anterior cruciate ligament reconstruction (ACLR) in an Asian population. Methods: We retrospectively reviewed prospectively collected data of 141 consecutive patients who underwent primary ACLR by a single surgeon, the senior author of this study. Flexion range, International Knee Documentation Committee (IKDC) score, KT-1000 translation, Tegner activity level scale, Lysholm score and satisfaction were assessed preoperatively and at 2 years postoperatively. The patients were then stratified into two groups: normal-BMI and high-BMI in accordance with WHO classification. Outcomes were then compared between the two groups. All statistical analysis were performed on IBM SPSS Statistics 20. Results: There were 81 patients in the normal-BMI group (BMI 18.5 to 24.9) and 60 patients in the high-BMI group (BMI ≥25). Preoperatively, the only differences were in the gender proportions as well as the pre-injury Tegner score. 2-years postoperatively, patients in the normal-BMI group had better flexion (139° versus 130°; P=0.0001), Tegner scores (5.7 versus 4.8; P=0.005) and satisfaction rate (99% versus 90%; P=0.041). There were no differences in graft failure or complication rates. Conclusions: Obese patients had poorer range of motion and Tegner scores as compared to their nonobese counterparts following primary ACLR.